Pedagogy and place : 100 years of architecture education at Yale - Stern, Robert A. M.; Stamp, Jimmy (Writer on architecture) (2016)
"Marking the centennial of the 1916 establishment of a professional program, Pedagogy and Place is the definitive text on the history of the Yale School of Architecture. Robert A.M. Stern, current dean of the school, and Jimmy Stamp examine its growth and change over the years, and they trace the impact of those who taught or studied there, as well as the architecturally significant buildings that housed the program, on the evolution of architecture education at Yale. Owing to the impressive number of notable practitioners who have attended or been affiliated with the school, this book also contributes a history, beyond Yale, of the architecture profession in the twentieth century. Featuring extensive archival research and illuminating firsthand accounts from alumni, faculty, and administrators, this well-rounded and engaging narrative is richly illustrated with historic photos of the school and its studios, images of student work, and important architectural achievements on and off campus."
Beginnings: toward an American Beaux-Arts, 1869-1916 -- An American Beaux-Arts, 1916-1947 -- An American Bauhaus? 1947-1958 -- A time of heroics, 1958-1965 -- Architecture or revolution? 1965-1971 -- Back to basics, 1971-1977 -- A brand-new school, 1977-1984 -- Rappel à l'ordre, 1985-1992 -- Toward urbanism, 1993-1998 -- Personal reflections on a new century by Robert A.M. Stern, 1998-2016.
Includes bibliographical references and index.
Keywords: Yale University. -- School of Architecture; Yale University. -- School of Architecture; Schools of architecture -- Connecticut -- New Haven -- History; Architecture -- Study and teaching (Higher) -- Connecticut -- New Haven; Architecture -- Study and teaching (Higher); Schools of architecture; Connecticut -- New Haven; History